The long way from α-error control to validity proper: problems with a short-sighted false-positive debate - Fiedler, Klaus; Kutzner, Florian; Krueger, Joachim I. (Perspectives on psychological science, 2012)
Several influential publications have sensitized the community of behavioral scientists to the dangers of inflated effects and false-positive errors leading to the unwarranted publication of nonreplicable findings. This issue has been related to prominent cases of data fabrication and survey results pointing to bad practices in empirical science. Although we concur with the motives behind these critical arguments, we note that an isolated debate of false positives may itself be misleading and counter-productive. Instead, we argue that, given the current state of affairs in behavioral science, false negatives often constitute a more serious problem. Referring to Wason’s (1960) seminal work on inductive reasoning, we show that the failure to assertively generate and test alternative hypotheses can lead to dramatic theoretical mistakes, which cannot be corrected by any kind of rigor applied to statistical tests of the focal hypotheses. We conclude that a scientific culture rewarding strong inference (Platt, 1964) is more likely to see progress than a culture preoccupied with tightening its standards for the mere publication of original findings.